Economic viability of Bordeaux mixture as a phytosanitary strategy in the cultivation of Theobroma cacao (GnosisWisdom, 2025)
A qualitative documentary methodology was applied to prepare this literature review, through a systematic review of scientific literature published between 2019 and 2024 in databases such as Scopus, SciELO, Redalyc, and Google Scholar, selecting 24 relevant studies that met criteria of timeliness, scientific rigor, and applicability. The findings highlight that Bordeaux mixture is effective in reducing the incidence of diseases in cocoa, accessible to small producers, and compatible with organic systems; however, its prolonged use can lead to copper accumulation in the soil, affecting the microbiota and sustainability of the agroecosystem. Therefore, its rational application is recommended, complemented by other integrated management practices, such as sanitary pruning, biological control, and phytosanitary monitoring. This review provides technical evidence to support the sustainable use of Bordeaux mixture and its integration into agroecological strategies for more resilient and environmentally responsible cocoa production.
Keywords: Theobroma cacao; economic viability; Bordeaux mixture; phytosanitary strategy